Interleukin-1 (IL-1) system gene expression in granulosa cells: kinetics during terminal preovulatory follicle maturation in the mare - Gérard Nadine; Martoriati Alain (BMC, 2003)
Abstract Background A growing body of evidences suggests that the ovary is a site of inflammatory reactions, and thus, ovarian cells could represent sources and targets of the interleukin-1 (IL-1) system. The purpose of this study was to examine the IL-1 system gene expressions in equine granulosa cells, and to study the IL-1β content in follicular fluid during the follicle maturation. For this purpose, granulosa cells and follicular fluids were collected from the largest follicle at the early dominance stage (diameter 24 ± 3 mm) or during the preovulatory maturation phase, at T0 h, T6 h, T12 h, T24 h and T34 h after induction of ovulation. Cells were analysed by RT-PCR and follicular fluids were studied by gel electrophoresis and immunoblotting. Results We demonstrated that interleukin-1β (IL-1β), interleukin-1 receptor 2 (IL-1R2) and interleukin-1 receptor antagonist (IL-1RA) genes are expressed in equine granulosa cells. We observed that the IL-1β and IL-1RA mRNA content changed in granulosa cells during the terminal follicular maturation whereas IL-1R2 mRNA did not vary. In follicular fluid, IL-1β content fluctuated few hours after induction of ovulation. Conclusions The expression of IL-1β gene in granulosa cells and the follicular fluid IL-1β content seem to be regulated by gonadotropins suggesting that IL-1β could be an intermediate paracrine factor involved in ovulation.